NATIONAL HOLIDAYS. CUSTOMS AND TRADITIONS IN UZBEKISTAN (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the multifaceted tapestry of national holidays, customs, and traditions in Uzbekistan. It provides an in-depth exploration of the country's rich cultural heritage, highlighting key celebrations such as Navruz, Independence Day, and various religious and cultural festivals. The piece elucidates the significance of each celebration, describing the customs, rituals, and communal practices associated with these events. Moreover, the article encapsulates the essence of Uzbekistan's cultural diversity, portraying the amalgamation of Islamic traditions, colorful festivals, wedding ceremonies, and artistic expressions. It effectively showcases the importance of hospitality, traditional attire, cuisine, and craftsmanship within Uzbek society, emphasizing their role in preserving the nation's identity and heritage. Additionally, the article admirably elucidates the intersection between historical customs and modern adaptations, highlighting Uzbekistan's ability to maintain its cherished traditions while embracing contemporary influences. It emphasizes the country's unity amidst cultural diversity and offers insights into cultural experiences for travelers seeking to immerse themselves in the rich tapestry of Uzbekistan's cultural landscape.